Growth and nutrient uptake response of cocoa seedlings (Theobroma cacao) to different growth media at the nursery - Mornyuie, A.O. (University of Energy and Natural Resources Sunyani Ghana, 2024)
A study was conducted in the nursery house of Mabang Megakarya Selection Programme, a substation of the Cocoa Research Institute of Ghana from April 2022 to September 2022 to determine the growth and nutrient uptake response of cocoa (Theobroma cacao) seedlings to different growth media at the nursery. The treatments comprised three base-materials viz: Topsoil (TS), Rice husk (RH) and Sawdust (SD) amended with three rates of rice husk biochar (RHB) at 75%: 25%, 50%:50% and 25%:75% and two rates of cocoa pod husk-based compost (CPHC) at 90%:10% and 80%:20% (base-media: amendment on v/v). The respective amounts of media combinations were mixed thoroughly and filled into polybags with dimensions 18 cm wide x 25 cm high. The treatments were arranged in a completely randomize design (CRD) with three replications. Seeds of cocoa hybrid clone C69 were sowed into the treatment pots. Cocoa seed germination was recorded at 14 and 17 days after sowing (DAS). Seedling growth and biomass production were measured at 2, 4 and 6 months after germination (MAG). Leaf nutrient concentration was analysed at six MAG and nutrient uptake calculated. Result indicated that at 14 DAS, seed germination was 100 % in potting media with TS50:RHB50 and 100 SD and these were significantly (p<0.05) higher than in all other treatments. The result showed that media type TS50:RHB50 significantly (p<0.05) increased number of leaves, plant height, stem diameter, tap root length, leaf chlorophyll content, leaf area and plant biomass production at 6 MAG. There was significant positive correlation between plant growth parameters at 6 MAG. Plant leave nutrients (N, P, K, Ca, and Mg) uptake were significantly (p<0.05) higher in potting media with TS50:RHB50 and TS90:CPHC10. Generally, TS50:RHB50 was the best growth media and produced vigorous cocoa seedlings.